Islamic Journalism in the Age of Algorithms: Between the Mission of Da'wah, Information Ethics, and the Logic of Digital Platforms - Wahyu Khoiruz Zaman (Journal of Communication Studies, 2024)
This article analyzes Islamic journalism in the algorithmic era by highlighting the relationship between the mission of da'wah, information ethics, and the logic of digital platforms. The development of digital media has changed the practice of Islamic journalism from just delivering religious information to a form of digital da'wah that operates in an algorithm-based system. This research uses a qualitative approach with a library research method through a descriptive-critical analysis of the literature on Islamic journalism, digital da'wah, information ethics, and digital platforms. The results of the study show that Islamic journalism faces a tension between the value of da'wah and the logic of the attention economy in digital platforms. On the one hand, Islamic journalism is required to maintain the principles of da'wah, tabayyun, accuracy, balance, and social responsibility. On the other hand, digital media encourages adaptation to click-based visibility mechanisms, engagement, virality, and content distribution optimization. This article offers an adaptive negotiation model that places da'wah, information ethics, and platform logic as elements that must be managed in a balanced manner. Islamic journalism in the age of algorithms should not reject digital technologies, but neither should it be completely subservient to the logic of platforms. Therefore, an adaptive, ethical, and credible Islamic communication model is needed so that the da'wah function continues to run effectively in the midst of changes in the digital media ecosystem.